Answer:
C
Step-by-step explanation:
Answer:
3
Step-by-step explanation:
if the inequality is 3, it will be 3
Answer:
16 meters
Step-by-step explanation:
Step 1:
They climbed 8 meters down
Then 8 meters up to get back to ground level.
Step 2:
8+8=16
Step-by-step explanation:
y = ax^n + bx^(n-1) ... + z
(0, 1) tells us that the constant term z = 1.
because x = 0 eliminates all other terms. and as the sum is 1, that means z = 1.
for the other pairs I strongly suspect
(-1, 3) : 2×(-1)² + 1 = 2×1 + 1 = 3
(-2, 9) : 2×(-2)² + 1 = 2×4 + 1 = 9
so, the fitting equation is
y = 2x² + 1